(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2022)
To determine the prevalence of work-related musculoskeletal disorders among OTs and PTs inSaudi, as well as to identify the factors that increase the likelihood of developing such a condition in thecourse of one’s career, researchers conducted a cross-sectional study to collect data on the number ofinjuries experienced by these professionals. The questionnaires were created using two previousinstruments that had been used with physical therapists in the past. There were a total of 19 questionson the questionnaire, ranging from basic biographical data to specifics on musculoskeletal diseases inthe workplace and the physiotherapy methods that may be used to treat them. Statistical Package for theSocial Sciences, version 16, was used to analyze the collected data. Study findings suggest that OTs andPTs have an elevated risk of WRI or WMSDs.